2010
DOI: 10.1364/ao.49.000267
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of range accuracy of range-gating laser radar using the centroid method

Abstract: An improved processing approach based on the relation between range accuracy and slicing number is proposed to improve the range accuracy of range-gating laser radar. The sequence of time-slice images is segmented according to their optimal slicing number and processed in segments to achieve the range information of objects. Experimental results indicate that the slicing number has a significant impact on range accuracy, and the highest range accuracy can be achieved when the systems work with an optimal slici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Later a modified approach to change threshold to suppress noise [4]. In 2010, Zhang, et al, presented the centroid method in research of setting threshold to suppress background noise [5].…”
Section: Introductionmentioning
confidence: 99%
“…Later a modified approach to change threshold to suppress noise [4]. In 2010, Zhang, et al, presented the centroid method in research of setting threshold to suppress background noise [5].…”
Section: Introductionmentioning
confidence: 99%
“…Depth resolution is one of the most critical issues of a lidar system [14][15][16][17][18][19][20][21] . In this Letter, we propose a threelaser-beam STIL system to improve the depth resolution of the STIL system.…”
mentioning
confidence: 99%
“…where I i is the gray value of the ith pixel. In general, we obtain the gray values and calculate the centroid on the time-resolved axis as the coordinate of the signal [19,20] :…”
mentioning
confidence: 99%
“…Finally, a 3D image can be reconstructed from multiple pulses by scanning the scene with a 1D laser fan beam [1,[12][13][14] . Range accuracy is one of the most critical features of imaging lidar systems [15][16][17] . Gleckler et al have reported that the achievable range error for an STIL system can be estimated by [5,7,8,18]…”
mentioning
confidence: 99%